Investigating the Nucleation, Growth, and Energy Levels of Organic Semiconductors for High Performance Plastic Electronics - Virkar, Ajay. (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2012)
This thesis details the progress made in improving the performance of organic transistors and the network conductivity of carbon nanotubes. The first section investigates organic semiconductor nucleation and growth on the most common dielectric surface used to fabricate organic thin film transistors. In the final section, lessons learned from studying organic semiconductor nucleation and growth were utilized to improve the conductivity of carbon nanotube networks. Selective nucleation of materials at the junctions between nanotubes in the network significantly decreased the network's sheet resistance. The resulting networks may be promising candidates for transparent electrodes with a variety of optoelectronic applications.